Effect of alpha-adrenoceptor antagonists on sexual function. A systematic review and meta-analysis - Rawa Bapir; Kamran Hassan Bhatti; Ahmed Eliwa; Herney Andrés García-Perdomo; Nazim Gherabi; Derek Hennessey; Vittorio Magri; Panagiotis Mourmouris; Adama Ouattara; Gianpaolo Perletti; Joseph Philipraj; Alberto Trinchieri; et al. (Archivio Italiano di Urologia e Andrologia, 2022)
Background: Alpha-adrenoreceptor antagonists or alpha-blockers are used in the treatment of hypertension, in the therapy of benign prostatic hyperplasia and in medical expulsive treatment of ureteral stones. These agents may affect the sexual function, with differences between drugs within the same class, depending on their selectivity for receptor subtypes. The aim of this review was to analyze the effects of alpha-blockers on sexual function. Materials and methods: We conducted a systematic review and meta-analysis by searching PubMed, EMBASE and other databases for randomized controlled trials (RCTs) reporting sexual adverse effects in patients treated with alpha-blockers. Odds ratios for sexual dysfunction were calculated using random effects Mantel-Haenszel statistics. Results: Out of 608 records retrieved, 75 eligible RCTs were included in the meta-analysis. Compared with placebo, alphablockers were associated with increased odds of ejaculatory disorders both in patients with lower urinary tract symptoms (LUTS) associated to benign prostatic hyperplasia (BPH) (OR: 7.53, 95% CI: 3.77-15.02, Z = 5.73, p < 0.00001, I2 = 55%) and in patients with ureteral stones (OR: 2.88, 95% CI: 1.50-5.44, Z = 3.19, p < 0.001, I2 = 31%). Uroselective alpha-blockers showed higher odds of ejaculatory disorders. Conversely, nonselective alpha-blockers were not associated with higher odds of ejaculatory dysfunction. Silodosin was associated with increased odds of ejaculatory dysfunction compared with tamsulosin (OR: 3.52, 95% CI: 2.18-5.68, 15 series, 1512 participants, Z = 5.15, p < 0.00001, I2 = 0%). Naftopidil and alfuzosin showed lower odds of ejaculatory dysfunction compared to uroselective alpha-blockers.No statistically significant differences in the odds of erectile dysfunction were observed when alpha-blockers were compared to placebo.